Evaluating the occurrence of increased postoperative cardiac enzymes in patients with coronary atherosclerotic obstruction - Zhang, Wanyi; Jin, Feng; Zhou, Heng; Wang, Wenzhi (Cellular and Molecular Biology, 2022)
Percutaneous transluminal coronary angioplasty (PTCA) has been accepted as the elective treatment in many patients with coronary atherosclerotic obstruction. A slight increase in cardiac markers after the percutaneous coronary intervention (PCI) has been commonly reported. Some researchers have suggested that it predicts mortality and long-term complications. This study aimed to evaluate the occurrence of increased postoperative cardiac enzymes and determine the relationship between such an increase and clinical angiographic and technical variables. For this purpose, the descriptive study was performed in Hospital’s cardiac ward from 2020-to 2021. One hundred twenty-two patients with stable coronary artery disease were studied for elective PTCA implanted with successful and uncomplicated stenting. Blood samples were taken from all patients to measure cardiac markers 20 hours after surgery. The normal range was CTnI ≤ 2ng/ml and CKMB ≤ 24 IU/L. Plasma levels of myocardial infarction and their relationship with clinical variables (including age, sex, risk factors for coronary artery disease, the severity of symptoms based on ccs class and previous history of acute coronary syndromes), angiographic including (lesion type, severity of stenosis) or related to the operation (operation on one or two vessels and direct stenting versus PTCA + stenting) were recorded in a questionnaire and observation sheets. The collected data were processed using descriptive statistics, frequency distribution tables, Chi-square, and student t-tests. Abnormal values of myocardial infarction were observed in 46.72% (57 patients). An increase in CTnI was observed in 39 patients (31.96%) and an increase in CKMB was seen in 31 patients (25.40%). Although the rise in CTnI exceeded the CKMB, the difference between the two was not statistically significant. The increased CTnI was significantly higher in older people, and the increase in CKMB was significantly higher in hypertensive individuals (p = 0.01). Based on the findings of this study, there is an increase in enzymes after successful and uncomplicated PCI selection. Increased CTnI occurs more frequently than CKMB. There is no relationship between enzyme enhancement and other clinical, angiographic, and technical variables.